Pharmacologic Management of Pain in Children: Balancing Evidence, Safety, and Clinical Challenges - Gianmarco Marcianò; Antonio Leo; Maria Cristina Caroleo; Riccardo Torta; Vincenzo Rania; Cristina Vocca; Caterina Palleria; Lucia Muraca; Alessandro Casarella; Domenica Scumaci; Luca Gallelli (Children, 2026)
Pain in children remains frequently underrecognized and undertreated despite significant advances in pediatric analgesia. The pharmacologic management of pediatric pain is challenging due to developmental differences in pharmacokinetics and pharmacodynamics, variability in drug metabolism, age-dependent responses, and the limited availability of high-quality pediatric clinical trials. This narrative review summarizes current evidence regarding the pharmacologic management of nociceptive, neuropathic, and nociplastic pain in children, integrating developmental pharmacology, efficacy data, safety considerations, and limitations of available evidence. A mechanism-based classification of pain provides a useful framework for therapeutic decision-making; however, clinical conditions often involve overlapping mechanisms requiring individualized and multidisciplinary approaches. Evidence supporting pharmacological interventions varies considerably according to pain type. Acetaminophen and NSAIDs remain the most used agents for nociceptive pain, while opioids retain a role in selected cases of moderate-to-severe pain under careful monitoring. Management of neuropathic and nociplastic pain remains particularly challenging due to limited pediatric trials, frequent off-label prescribing, and reliance on extrapolation from adult populations. Future research should focus on age-specific randomized controlled trials, pharmacokinetic and pharmacogenomic variability, long-term safety outcomes, and integration of pharmacologic treatments within multimodal pain management strategies.